MON-359 Hollow Bones: A Case Report of Immobilization Osteoporosis in a Young Female - Bhat, Salman Zahoor (J Endocr Soc, 2020)
Abstract Introduction: Osteoporosis is defined as decreased bone strength due to reduced bone mineral density (BMD) and/or abnormal bone architecture leading to bone fragility and increased risk of pathologic fractures. Typically a disease of post-menopausal females, osteoporosis is uncommon in the young. We present a case of a 34-year-old woman, who was diagnosed with severe osteoporosis in the setting of prolonged immobilization. Clinical Case: A 34-year-old woman was admitted for treatment of bacteremia in the setting of IV drug use and right hip septic arthritis leading to femoral head osteonecrosis requiring a long course of antibiotic treatment and resulting in prolonged immobilization. She was readmitted 2 months later with septic shock and bilateral septic arthritis needing right hip replacement for source control. She developed multiple contractures of lower extremities due to prolonged immobility and was immobile for a total of 11 months despite significant physical therapy (PT) involvement. A few months into her hospital stay, she developed acute onset right ankle pain with no falls or trauma. Xrays showed right tibial metaphyseal fracture and severe demineralization of bones of lower extremities. History and physical exam showed no signs/symptoms of malabsorption, hyperthyroidism or Cushing’s syndrome. Laboratory evaluation showed calcium (Ca) of 11.8 mg/dL (8.5–10.4), parathyroid hormone (PTH) < 3 ng/dL (12–72), C-telopeptide (Ctx) 1806 pg/ml (60–650) and normal phosphate, TSH, prolactin, 25-hydroxy and 1,25-dihydroxy vitamin D levels. PTHrP (parathyroid hormone related peptide) was < 2 pmol/L. 24-hour urine Ca was 414 mg (50–150). Serum and urine protein electrophoresis showed no monoclonal spike. Gonadal profile showed estrogen 42 pg/dL, FSH 1 mU /mL, LSH 0.1 mU /mL. DEXA scan showed severe osteoporosis with T-score of -3.2 at both the left femoral neck and lumbar spine. Osteoporosis and hypercalcemia were attributed to protracted immobilization. Therapy was initiated with alendronate 70 mg weekly along with vitamin D. Teriparatide was not used due to high serum Ca. Repeat labs at 6 months showed good response to alendronate with Ca 9.6, PTH 58, 24 hr urine Ca 96 and Ctx 1092. Mobilization of patient and regular PT were performed. Conclusion: Osteoporosis in a young adult is a rare entity and demands evaluation for secondary causes. An important and overlooked cause of bone loss is immobility and decreased load development on bones. Bone is a piezoelectric material and immobilization causes negative bone turnover. Early physical mobility and weight bearing is the most effective method of reducing bone loss. Teriparatide, due to anabolic effects has an advantage over bisphosphonates. Romosozumab (anti-sclerostin antibody) and whole body vibration are also being studied for disuse osteoporosis. Calcium and vitamin D supplementation are essential.